(3eLdS GdeMGSHI GdLRGFQj (B:s (3GdJfXje hGdGNJUGUGJ (B/s - (3Thbj, jYjT JeGes ((3GdGScfOQjI (B: s (3ecJHI GdhaGA GdbGfhfjI(B, s, 2021)
(3jVe GdEWGQ GdYVhj deLdS GdeMGSHI efgG GdCMcGe GdfGXeI ddJTcjdI GdbVGFjI deLdS GdeMGSHI hGdCMcGe GdfGXeI ddJQcjHI GdgjcdI deLdS GdeMGSHI, GdEWGQ GdhXjaj deLdS GdeMGSHIHeG ajg MOhO GdUdGMjGJ GdeefhMI deLdS GdeMGSHI hBdjGJ Yed eLdS GdeMGSHI hGdBKGQ GdeJQJHI YdjgG(B.s
(3HjHdjhZQGajG(B: (3U U(B139-147s
Keywords: (3GdeLGdS GdGbJUGOjI s; (3GdeMGSHIs; (3GdeMGSHI GdGOGQjIs